1972
DOI: 10.1136/hrt.34.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of ageing changes in the human sinoatrial node and internodal tracts.

Abstract: Quantitative analysis of the amount of muscle,fat, and collagen in the human sinoatrial node and internodal tracts has been carried out. Subjects under 50 were compared with those over 75 years of age at death. In old age there is a significant fall in the amount of muscle present in the sinoatrial node and internodal tracts.It has long been accepted that the sinoatrial node is the normal pacemaker of the heart. More recently it has been established that specialized atrial myogenic conduction paths carry the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(52 citation statements)
references
References 6 publications
1
49
1
1
Order By: Relevance
“…Such acquired anatomic barriers confirmed the previous studies that atrial fibrosis could be found in patients with rheumatic 7,10,11 and nonrheumatic heart disease, such as hypertrophic or dilated cardiomyopathy and coronary artery disease, 7,12 and even in aging without structural heart disease. 7,13 However, the ESAs or LDPs were variably located in those patients, even in patients with the same disease. Our findings suggest that the atrial fibrosis may be related not only to mechanic overload but also to some unknown atrial myopathy.…”
Section: Discussion Anatomic Barriers For Lamrtmentioning
confidence: 99%
“…Such acquired anatomic barriers confirmed the previous studies that atrial fibrosis could be found in patients with rheumatic 7,10,11 and nonrheumatic heart disease, such as hypertrophic or dilated cardiomyopathy and coronary artery disease, 7,12 and even in aging without structural heart disease. 7,13 However, the ESAs or LDPs were variably located in those patients, even in patients with the same disease. Our findings suggest that the atrial fibrosis may be related not only to mechanic overload but also to some unknown atrial myopathy.…”
Section: Discussion Anatomic Barriers For Lamrtmentioning
confidence: 99%
“…Our method has similarities to that used by some authors such as Reginald Hudson [8] in 1960, Davies [9] in 1972 and Kenneth Anderson [10] in 1979, all in Britain, which after removal of the sinoatrial node, made vertical cuts for the first two, and mixed, vertical and cross-sections for the last.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that there is clear evidence in the human atrial myocardium of age-related electrical uncoupling of the side-to-side connections between bundles. This is histologically related to the proliferation of extensive collagenous tissue septa in intracellular spaces [4][5][6]. In pathological studies, it was demonstrated that these age-induced changes include a reduction in the number of myocardial cells within the sinus node, a generalized loss of atrial myocardial fibers, as well as an increase in fibrosis which leads to an apparent loss of myocardial fiber continuity [1][2][3][4][5][6].…”
Section: Editorialmentioning
confidence: 99%